SAT0540 Gout Patients Treated with Conventional Urate-Lowering Therapy: Association between Disease Control and Work Productivity. (10th June 2014) - Wood, R.; Johnson, J.; Morlock, R.; Baumgartner, S.; Ramachandran, S.
Abstract : Background: Inadequate control of hyperuricaemia in gout patients can lead to loss of work productivity, activity limitations [1] and higher gout-related treatment costs [2]. Some patients treated with conventional urate-lowering therapy (ULT) are inadequately controlled [3]. Objectives: To evaluate the impact of inadequate control on work productivity and activity limitations in gout patients. Methods: A retrospective database analysis of gout patients currently receiving conventional ULT for at least 3 months. Data were drawn from the Adelphi Disease Specific Programme (DSP)™, a cross-sectional survey of patients with gout in France, Germany, UK and US. Participating physicians submitted extensive clinical data for each patient including most recent serum uric acid (sUA) level and number of flares in last 12 mos. Patients were invited to complete a patient self-completion questionnaire, containing the Work Productivity and Activity Impairment (WPAI) questionnaire. Inadequate control was defined as sUA level >6 mg/dL or ≥2 flares. Adequate control was defined as sUA level ≤6 mg/dL and 0 flares. Mann-Whitney tests investigated differences between inadequately and adequately controlled patients in productivity measured by WPAI. Results: Of 1204 gout patients in this analysis, 836 (69%) were inadequately controlled; 82% of patients were male, mean age was 61 yrs, and mean duration on current ULT was 32 mos. 368 (31%) patients were adequately controlled with a mean age of 63 yrs and mean duration on current ULT of 57 mos. There were no significant differences between patients deemed adequately controlled vs inadequately controlled on number of renal, autoimmune, GI or CV comorbidities. Inadequately controlled patients were significantly more impaired by gout compared to adequately controlled patients (Work time missed: 4.50% vs 1.34%, p=0.0003; Impairment while working: 19.08% vs 5.17%, p<0.0001; Overall work impairment: 20.40% vs 5.57%, p<0.0001; Activity impairment: 20.34% vs 5.28%, p<0.0001). Conclusions: Only 31% of gout patients currently treated with a ULT were adequately controlled. Inadequately controlled patients reported greater impairment in productivity. Gout treatment strategies to improve control of hyperuricaemia may lead to improvement in productivity. References: Perry M. Rheumatology (Oxford) 2010;49:2233-4. Saseen JJ. Rheumatology (Oxford) 2012;51:2004-12. Perez-Ruiz F. Adv Ther 2012;29:935-46. Acknowledgements: Research sponsored by Ardea Biosciences/AstraZeneca. Disclosure of Interest: R. Wood Employee of: Adelphi Real World, J. Johnson Employee of: Adelphi Real World, R. Morlock Employee of: Ardea Biosciences, Inc, S. Baumgartner Employee of: Ardea Biosciences, Inc, S. Ramachandran Employee of: AstraZeneca DOI: 10.1136/annrheumdis-2014-eular.4482